INFLATED LEVELS OF SCFA, BIFIDOBACTERIA AND LACTOBACILLUS IMPROVES THE STATUS OF PRE HYPERTENSION AND TYPE 2 DIABETES MELLITUS IN SUBJECTS RESIDING IN NORTH EAST INDIA–A RANDOMIZED CONTROL TRIAL WITH SYNBIOTIC SUPPLEMENTATION - Sheth, Mini; Chand, Vasundhra; Thakuria, Abnita (International Journal of Current Pharmaceutical Research, 2015)
Objective: The study was undertaken to determine the effect of synbiotic supplementation on glycemia, gut health and Short chain fatty acid (SCFA) levels in pre hypertensive type 2 diabetic adults. Methods: 60 pre hypertensive adults with type II NIDDM aged 35-55yrs were purposively selected from Sun Valley Hospital, form north east state of India, and based on the informed consent given by the subjects they were randomly divided into Control (N=10) and Experimental groups (N=25). The experimental group was supplemented with 1 gm of freeze dried synbiotic product (2 species of Lactobacillus, Bifidobacterium each, one species of Streptococcus, one species of yeast along with 300 mg Fructo oligosaccharide) daily to be taken along with meals, for 45 days. Glycemic parameters were determined using an enzymatic method. DNA was isolated from the stool samples and was quantified for determination of LAB, Bifidobacteria and Enteric pathogens using PCR techniques. SCFA was determined using Gas Chromatography Mass Spectrophotometer (GCMS). Results: Intervention with synbiotic supplementation resulted in a significant reduction in FBS, PP2BS, HbA1c, by 3.3%, 6.7%, 14%, respectively along with a significant increment in butyrate (547.4%) and propionate (310%) levels. Gut health of the subjects improved significantly as indicated by increased colonization of Bifidobacteria (131.6%) and LAB (32.6%) and a significant reduction in enteric pathogens (44.6%). Conclusion: Daily intake of 1 g freeze dried synbiotic product is an attractive therapy to improve glycemia, gut health which may be implicated by increased production of SCFA.